The Impact of Environmental Hazards on the Academic Performance of Public Secondary School Students - Ucheje, Okoroafor Okechukwu; Balafama, Ipalibo-Wokoma (Three E Science Institute, 2025)
Environmental factors significantly influence students' academic performance, with hazardous conditions posing notable impediments to educational outcomes. This study investigated the impact of environmental hazards—air pollution, noise pollution, and flooding—on the academic performance of students in public secondary schools in the South-South region of Nigeria. Three objectives and corresponding hypotheses guided the research. Employing a correlational survey design, the study targeted all principals of public secondary schools in the region. A purposive sampling technique was used to select a sample of 240 principals representing six states in South-South Nigeria. Data were collected using two self-designed instruments: the Environmental Hazards Questionnaire (EAQ) and the Academic Performance Questionnaire (APQ). Reliability testing of the instruments yielded coefficients of 0.91 and 0.88, respectively, indicating high reliability. Data analysis was conducted using simple regression to address the research questions, while hypotheses were tested using the t-test associated with simple regression at a 0.05 significance level. The results revealed that air pollution, noise pollution, and flooding have a significant and negative impact on students' academic performance. Specifically, air pollution contributes to health issues that disrupt students’ focus and attendance, while noise and flooding interfere with the learning environment and academic activities. The study concluded that mitigating these environmental hazards is essential for enhancing academic performance in public secondary schools. Recommendations include implementing policies to minimize air and noise pollution around school environments and adopting effective flood management strategies to safeguard academic infrastructure and activities.